1960
DOI: 10.1136/jcp.13.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Asthma, With Special Reference to Changes in the Bronchial Mucosa

Abstract: The pathological features of 20 cases dying in status asthmaticus have been studied. In gross sections the lungs showed no emphysema, but mucus plugs in the air passages and focal areas of collapse were outstanding features. Five cases showed cystic bronchiectasis which was of a similar distribution to the focal areas of collapse, occurring in the upper lobes as commonly as in the lower lobes.Histologically, shedding of the ciliated bronchial mucosal cells was prominent and this is attributed to a transudation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
413
1
8

Year Published

1965
1965
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 964 publications
(436 citation statements)
references
References 11 publications
14
413
1
8
Order By: Relevance
“…Early histological studies of lung tissue taken at post-mortem from subjects who died of status asthmaticus demonstrated the presence of mucus plugs in airway passages, loss of ciliated respiratory epithelium, and thickening of BM, infiltration of eosinophils, oedema and ASM hypertrophy, now collectively termed 'airway remodelling' [4]. Further studies in subjects with asthma were the first to confirm that changes in the airway vasculature are associated with remodelling of the airway wall [7,8].…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Early histological studies of lung tissue taken at post-mortem from subjects who died of status asthmaticus demonstrated the presence of mucus plugs in airway passages, loss of ciliated respiratory epithelium, and thickening of BM, infiltration of eosinophils, oedema and ASM hypertrophy, now collectively termed 'airway remodelling' [4]. Further studies in subjects with asthma were the first to confirm that changes in the airway vasculature are associated with remodelling of the airway wall [7,8].…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 99%
“…Asthma studies were the first to confirm that changes in the bronchial vasculature are associated with remodelling of the airway wall [4][5][6][7][8]. Thereafter, a number of studies reported the involvement of specific growth factors, such as fibroblast growth factor (FGF), transforming growth factor (TGF) β1 and vascular endothelial growth factor (VEGF), during vascular remodelling in asthma and COPD [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines also induce the secretory form of phospholipase A 2 from airway smooth muscle cells [24]. Cultured human airway smooth muscle cells express mRNA for enzymes of the 5-lipoxygenase pathway, including 5-lipoxygenase, epoxide hydrolase, leukotriene (LT)C 4 synthase and c-glutamyl transpeptidase, as well as receptors for LTB 4 and Cys-LT 1 receptors [25]. The expression of these enzymes and receptors was increased following exposure to human atopic serum or to IL-1b.…”
Section: Products Of Lipid Metabolismmentioning
confidence: 99%
“…Morphometric studies of airway smooth muscle in asthma have demonstrated that there is an increase in airway smooth muscle mass which is accounted for by hyperplasia and also by hypertrophy [4,5]. Such an increase in airway smooth muscle mass could contribute to the exaggerated airway narrowing observed in asthma [6,8] and may result from the action of growth factors released during the chronic inflammatory process.…”
mentioning
confidence: 99%
“…The link between abnormal airway physiology and airway inflammation was initially suggested by the results of post-mortem studies of asthmatic lungs which documented the presence of an inflammatory infiltrate (Dunnill 1960). The use of fibreoptic bronchoscopy has allowed bronchial biopsies and lavage fluid to be examined in less severe asthmatics and in normal subjects.…”
Section: Asthma and Allergic Inflammationmentioning
confidence: 99%